To Compare Efficacy of Hypnosis and Intravenous Sedation in Controlling of Important Variables of Vital Signs and Evaluate the Patient Anxiety Before and after Topical Anesthesia in Ophthalmic Surgery - Behnaz, Faranak; Solhpour, Ali (Novelty in Biomedicine, 2016)
Background: Stress is one of the most important problems among preoperative patients. In order to reduce these signs and symptoms, some medications are used for patients. The aim of this study was to compare the efficacy of hypnosis to intravenous sedation on controlling the important variables of vital signs and to evaluate the patient anxiety before and after regional or topical anesthesia in ophthalmic surgery. Materials and Methods: This study was designed as a double-blind stratified randomized clinical trial. Hypnotism was administered to hypnotism group, and midazolam, fentanyl, and propofol were given intravenously to the IV sedation group. The patients were monitored and the baseline variables consisted of mean arterial pressure, pulse rate, respiratory rate, and O2 saturation were registered every 15 minutes during surgery. Patient anxiety was measured via Spielbeger`s State Anxiety Index (STAI) score before and after surgery. Results: 90 patients were participated in the study, with 50% (n=45) assigned to hypnosis group and 50% (N=45) assigned to IV sedation group. Patients characteristics, including age, gender, and body mass index (BMI) duration of surgery were similar among the groups (P>0.05). Spielbeger`s State Anxiety Index (STAI) score before and after surgery were not significantly different in both groups (P>0.05). Heart rate, respiratory rate, mean arterial pressure were lower among hypnosis group as well as this group had higher O2 saturation during surgery (P<0.05). Conclusion: Hypnosis can be an effective means of controlling vital signs at different intervals of starting the ophthalmic surgery compared to intravenous sedation. In the hypnosis group anxiety was similar to IV sedation group, but O2 saturation was more desirable.